Penerapan Model Kanvas dalam Pendampingan Tenaga Kerja Mandiri Pemula untuk Perencanaan Bisnis di Kelurahan Pematang Kandis, Kecamatan Bangko, Kabupaten Merangin: Pengabdian - Hamdiah; Febby Nanda Utami; Heriyani; Dahlia; Suci Wulandari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The mentoring program for novice independent workers in Pematang Kandis Village aims to increase the entrepreneurial capacity of the community through the understanding and application of the Business Model Canvas (BMC) as a simple and systematic business planning tool. This activity is motivated by the still low competitiveness and managerial capabilities of novice independent workers in developing sustainable business plans, due to limited access to training and business planning or the still low capabilities of Human Resources. Mentoring through this program can be an important instrument in developing local entrepreneurial potential by implementing activity implementation methods including socialization, training, focus group discussions, and individual assistance in preparing the BMC consisting of customer segments, value propositions, distribution channels, customer relationships, revenue streams, key resources, main activities, key partners, and cost structures. Participants also showed an increased understanding of the importance of mature and systematic business planning. This activity is expected to be the first step in creating resilient and competitive independent entrepreneurs.